TINGKAT STRES AKADEMIK DAN RISIKO EATING DISORDER PADA MAHASISWA GIZI TINGKAT AKHIR UNIVERSITAS BRAWIJAYA: A CROSSECTIONAL STUDY - Zulhadiman, Zulhadiman; Yuhasnara, Sofhin Madison; Muslihah, Nurul (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2024)
ABSTRACTBackground: Strict educational curricula, many assignments, and changes between practice areas can increase academic stress in medical students. This is then supported by various other factors, resulting in a higher prevalence of academic stress in health students than students of other majors. While some stress levels can motivate and increase student productivity, excessive and prolonged stress can also cause adverse effects, such as the risk of eating disorders.Objectives: To analyze the relationship between academic stress levels and the risk of eating disorders in final-year nutrition and dietetic students at Brawijaya University.Methods: This research is a quantitative study with a cross-sectional design. The sample comprised 132 students in the Dietitian Profession study program and Bachelor of Nutrition Science at Brawijaya University. The sampling technique used saturated sampling, meaning that the entire population is sampled. Data was collected using the Perceived Academic Stress Scale (PASS) and Eating Attitude Test-26 (EAT-26) questionnaires. The data were analyzed using the Spearman rank correlation test.Results: 96 respondents (72.7%) experienced moderate academic stress, 16 respondents (12.1%) experienced severe academic stress, and 43 respondents (32.6%) were at risk of experiencing eating disorders. There is a significant relationship between the level of academic stress and the risk of eating disorders with positive direction and weak strength (p = 0,000, r = 0,349).Conclusion: There is a significant and positive relationship with weak power between the level of academic stress and the risk of eating disorders in final-year Nutrition and Dietetic students at Brawijaya University. Thus, the higher the level of academic stress, the higher the risk of eating disorders.Keywords: academic stress level; risk of eating disorders; student ABSTRAKLatar belakang: Kurikulum pendidikan yang ketat, banyaknya tugas, dan perpindahan antar wahana praktik dapat meningkatkan stres akademik pada mahasiswa kesehatan. Ditunjang dengan berbagai faktor lain, mengakibatkan prevalensi stres akademik yang terjadi pada mahasiswa kesehatan lebih tinggi dibandingkan mahasiswa jurusan lainnya. Sementara beberapa tingkat stres dapat memotivasi dan meningkatkan produktivitas mahasiswa, stres yang berlebihan dan berkepanjangan juga dapat menyebabkan efek buruk, seperti risiko eating disorder.Tujuan: Menganalisis hubungan antara tingkat stres akademik dan risiko eating disorder pada mahasiswa gizi tingkat akhir.Metode: Pendekatan penelitian yang ditetapkan adalah kuantitatif dengan desain cross-sectional. Populasi penelitian berjumlah 132 mahasiswa dari program studi Profesi Dietisien dan S1 Ilmu Gizi Universitas Brawijaya, Kota Malang, Indonesia. Teknik sampel yang ditetapkan adalah sampling jenuh. Data dikumpulkan menggunakan kuesioner berkaitan dengan Perceived Academic Stress Scale (PASS) dan Eating Attituted Test-26 (EAT-26). Data yang telah dikumpulkan kemudian dianalisis menggunakan uji spearman rankHasil: Sebanyak 96 responden (72,7%) mengalami stres akademik sedang, 16 responden (12,1%) mengalami stres akademik berat, dan 43 responden (32,6%) berisiko mengalami eating disorder. Terdapat hubungan yang signifikan antara tingkat stres akademik dan risiko eating disorder dengan arah positif dan kekuatan lemah (p = 0,000, r = 0,349).Simpulan: Ada hubungan yang signifikan dan positif antara tingkat stres akademik dengan risiko eating disorder pada mahasiswa tingkat akhir Gizi dan Dietisien Universitas Brawijaya. Dengan demikian, semakin tinggi tingkat stres akademik maka semakin tinggi risiko terjadinya eating disorder.Kata kunci: tingkat stres akademik; risiko eating disorder; mahasiswa